The neurovascular unit in diffuse intrinsic pontine gliomas - El-Khouly, Fatma E.; Haumann, Rianne; Breur, Marjolein; Veldhuijzen van Zanten, Sophie E.M.; Kaspers, Gertjan J.L.; Hendrikse, N. Harry; Hulleman, Esther; van Vuurden, Dannis G.; Bugiani, Marianna (Free Neuropathology, 2021)
Aims: Diffuse intrinsic pontine glioma (DIPG) is a childhood brainstem tumor with a median overall survival of eleven months. Lack of chemotherapy efficacy may be related to an intact blood-brain barrier (BBB). In this study we aim to investigate the neurovascular unit (NVU) in DIPG patients. Methods: DIPG biopsy (n = 4) and autopsy samples (n = 6) and age-matched healthy pons samples (n = 20) were immunohistochemically investigated for plasma protein extravasation, and the expression of tight junction proteins claudin-5 and zonula occludens-1 (ZO-1), basement membrane component laminin, pericyte marker PDGFR-β, and efflux transporters P-gp and BCRP. The mean vascular density and diameter were also assessed. Results: DIPGs show a heterogeneity in cell morphology and evidence of BBB leakage. Both in tumor biopsy and autopsy samples, expression of claudin-5, ZO-1, laminin, PDGFR-β and P-gp was reduced compared to healthy pontine tissues. In DIPG autopsy samples, vascular density was lower compared to healthy pons. The density of small vessels (<10 µm) was significantly lower (P<0.001), whereas the density of large vessels (≥10 µm) did not differ between groups (P = 0.404). The median vascular diameter was not significantly different: 6.21 µm in DIPG autopsy samples (range 2.25-94.85 µm), and 6.26 µm in controls (range 1.17-264.77 µm). Conclusion: Our study demonstrates evidence of structural changes in the NVU in DIPG patients, both in biopsy and autopsy samples, as well as a reduced vascular density in end-stage disease. Adding such a biological perspective may help to better direct future treatment choices for DIPG patients.